KSHV Rta Promoter Specification and Viral Reactivation - Guito, Jonathan; Lukac, David M. (Frontiers in microbiology, 2012)
Viruses are obligate intracellular pathogens whose biological success depends upon replication and packaging of viral genomes, and transmission of progeny viruses to new hosts. The biological success of herpesviruses is enhanced by their ability to reproduce their genomes without producing progeny viruses or killing the host cells, a process called latency. Latency permits a herpesvirus to remain undetected in its animal host for decades while maintaining the potential to reactivate, or switch, to a productive life cycle when host conditions are conducive to generating viral progeny. Direct interactions between many host and viral molecules are implicated in controlling herpesviral reactivation, suggesting complex biological networks that control the decision. One viral protein that is necessary and sufficient to switch latent Kaposi's sarcoma-associated herpesvirus (KSHV) into the lytic infection cycle is called K-Rta. K-Rta is a transcriptional activator that specifies promoters by binding DNA directly and interacting with cellular proteins. Among these cellular proteins, binding of K-Rta to RBP-Jk is essential for viral reactivation. In contrast to the canonical model for Notch signaling, RBP-Jk is not uniformly and constitutively bound to the latent KSHV genome, but rather is recruited to DNA by interactions with K-Rta. Stimulation of RBP-Jk DNA binding requires high affinity binding of Rta to repetitive and palindromic "CANT DNA repeats" in promoters, and formation of ternary complexes with RBP-Jk. However, while K-Rta expression is necessary for initiating KSHV reactivation, K-Rta's role as the switch is inefficient. Many factors modulate K-Rta's function, suggesting that KSHV reactivation can be significantly regulated post-Rta expression and challenging the notion that herpesviral reactivation is bistable. This review analyzes rapidly evolving research on KSHV K-Rta to consider the role of K-Rta promoter specification in regulating the progression of KSHV reactivation.